THE EFFECTS OF IRON DEFICIENCY ANEMIA ON A PREGNANT WOMAN'S BODY - Sodikova Shoira Amriddinovna; To’lqinov Yashnarbek; Ubaydullayev Shuhratjon (European Science Publishing, 2025)
Iron deficiency anemia (IDA) is one of the most common blood deficiency diseases in pregnant women and can seriously affect the health of the mother and fetus. This article reviews the causes of iron deficiency anemia, its negative effects on the pregnant woman's body and fetus. The main consequences of IDA include fatigue, cardiovascular problems, weakened immunity, fetal growth retardation, premature birth and low birth weight. The article also highlights the prevention and treatment of IDA, including the importance of iron-fortified nutrition, iron supplements, and regular medical examinations. This article provides comprehensive and useful information about iron deficiency anemia for pregnant women and healthcare professionals.
Keywords: Iron deficiency anemia, pregnant woman, hemoglobin, oxygen, fetal development, iron supplements, medical examination.